Sistem Pencatatan Kehadiran Deteksi Wajah Menggunakan Metode Haar Feature Cascade Classifier - Miftah Khul Janah; Veronica Lusiana (Universitas Nasional, 2021)
Biometric innovation is one source that can be used in security frameworks such as facial recognition as personal information. The human face has a lot of data and has the most normal and widely used attributes for the presentation of human character. As well as communicating feelings and considerations, faces can also be used to identify individuals. One of the innovations in the recognition statement applied to biometrics is the use of the human face as a recording system in the field of education. However, there are several circumstances related to the recording of student absenteeism currently occurring in the field of education, namely